Pengaruh Lingkungan Kerja dan Karakteristik Individu Terhadap Kinerja Karyawan PT. Bumi Mineral Sulawesi - Rahma Azis (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of the study was to analyze the effect of work environment and individual characteristics partially and simultaneously on the performance of employees of PT Bumi Mineral Sulawesi. The type of research used is quantitative research. The population of this study were all permanent employees of PT Bumi Mineral Sulawesi, totaling 525 people. The sampling technique using the Slovin formula amounted to 84 respondents. The data analysis technique used is multiple linear regression. The results showed that the work environment had a positive and significant effect partially on employee performance at PT Bumi Mineral Sulawesi. While individual characteristics partially do not affect employee performance at PT Bumi Mineral Sulawesi. Simultaneously, the work environment and individual characteristics have a positive and significant influence on the performance of employees of PT Bumi Mineral Sulawesi, with a large influence of 11.8%, while the remaining 88.2% is influenced by other variables outside this study.